Governance Reform: Getting the Fit Right. (8th December 2015) - Levy, Brian
Summary: This article builds on recent literature on political settlements and new institutional economics to suggest a "good‐fit" alternative to the "best practices" approaches that until recently have dominated efforts at governance reform. It introduces a typology for distinguishing systematically among different groups of countries and maps the typology to four alternative approaches to governance reform. The article then offers a set of "good‐fit" hypotheses as to the conditions under which each of the approaches is likely to be effective. Copyright © 2015 John Wiley & Sons, Ltd.